2014
DOI: 10.1039/c4ra09797a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-alkyl pyrroles via decarboxylation/dehydration in neutral ionic liquid under catalyst-free conditions

Abstract: A general route to N-alkyl pyrroles by reacting aromatic, heteroaromatic or aliphatic aldehydes with 4hydroxyproline in ionic liquid under neutral condition was developed. The ionic liquid can be readily recovered and reused up to 5 reaction cycles without any effect on the yield of the product formed. The utility of the protocol for one-pot synthesis of 9H-benzo[e]pyrrolo[2,1-b][1,3]oxazines is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Thus, development of a new synthetic protocols for prolinamide synthesis employing readily available starting materials is an attractive synthetic target. Considering the widespread use of isonitriles for multicomponent reactions (MCR) and in our interest in decarboxylative reactions and isonitrile insertions, we envisioned that decarboxylative MCR between l -proline, aldehyde, and isonitrile would offer a new metal-free approach to N -substituted prolinamides. It is worth mentioning that Ugi et al have reported a four-component MCR between an α-amino acid, aldehyde, isonitrile and alcohol to produce 1,1′-iminodicarboxylic acid derivatives .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, development of a new synthetic protocols for prolinamide synthesis employing readily available starting materials is an attractive synthetic target. Considering the widespread use of isonitriles for multicomponent reactions (MCR) and in our interest in decarboxylative reactions and isonitrile insertions, we envisioned that decarboxylative MCR between l -proline, aldehyde, and isonitrile would offer a new metal-free approach to N -substituted prolinamides. It is worth mentioning that Ugi et al have reported a four-component MCR between an α-amino acid, aldehyde, isonitrile and alcohol to produce 1,1′-iminodicarboxylic acid derivatives .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we got interested in carrying out the detailed optimization study and finding the mechanistic rationale of this metal-free decarboxylation reaction. Our initial focus was on the screening of various ionic liquids as they have shown potential in decarboxylation reactions . Thus, using [bmim]­Br, decarboxylative coupling of 1a (0.75 mmol), 2a (0.85 mmol), and 3a (1.00 mmol) afforded propargylamine 4a in 38% yield (Table ; entry 2) while using [bmim]­OAc, 4a could be obtained in 15% yield (Table ; entry 1).…”
Section: Results and Discussionmentioning
confidence: 99%